Mathematics and Mother Tongue Academic Achievement - Nunes, Catarina (2022)
Nunes, C., Beatriz-Afonso, A., Cruz-jesus, F., Oliveira, T., & Castelli, M. (2022). Mathematics and Mother Tongue Academic Achievement: A Machine Learning Approach. Emerging Science Journal, 6(Special Issue: Current Issues, Trends, and New Ideas in Education), 137-149. https://doi.org/10.28991/ESJ-2022-SIED-010 ----This study was funded by FCT – Fundação para a Ciência e Tecnologia (DSAIPA/DS/0032/2018). Acknowledgements: We also gratefully acknowledge financial support from FCT Fundação para a Ciência e a Tecnologia (Portugal), national funding through research grant Information Management Research Center – MagIC/NOVA IMS (UIDB/04152/2020).